The Monogamy Paradox: What Do Love and Sex Have to Do With It? - Carter, C. Sue; Perkeybile, Allison M. (Frontiers in Ecology and Evolution, 2018)
Genetic monogamy is rare - at least at the level of a species – and monogamy can exist in the absence of sexual fidelity. Rather than focusing on mating exclusivity, it has become common to use the term “social monogamy” to describe a cluster of social features, including the capacity for selective and lasting social bonds, central to what humans call “love.” Socially monogamous mammals often exhibit selective aggression toward strangers and form extended families. These features of social monogamy in mammals are supported by patterns of hormonal function originating in the neurobiology of maternity, including oxytocin, as well as a more primitive vasopressin pathway. Another key feature of social monogamy is reduced sexual dimorphism. Processes associated with sexual differentiation offer clues to the mysteries surrounding the evolution of monogamy. Although there is consistency in the necessary ingredients, it is likely that there is no single recipe for social monogamy. As reviewed here, genes for steroids and peptides and their receptors are variable and are subject to epigenetic regulation across the lifespan permitting individual, gender and species variations and providing substrates for evolution. Reduced sensitivity to gonadal androgens, and a concurrent increased reliance on vasopressin (for selective defense) and oxytocin (for selective affiliation) may have offered pathways to the emergence of social monogamy.